Urdu translation of the Sahin–Francis Scale of Attitude toward Islam Revised: a response and update to Francis, Tekke, and Robbins (2016). Issue 5 (27th May 2016) - Musharraf, Sadia; Lewis, Christopher Alan
ABSTRACT: As part of an ongoing initiative that has sought to refine the Sahin–Francis Scale of Attitude toward Islam for use when measuring attitude to Islam in different cultural contexts, the Sahin–Francis Scale of Attitude toward Islam Revised has recently been developed. To facilitate further research with this new scale, the present study provides an Urdu translation of the Sahin–Francis Scale of Attitude toward Islam Revised.